Response to the article “Bickerstaff brainstem encephalitis, acute transverse myelitis, and acute motor axonal neuropathy: diagnostic and treatment challenges in patients with concomitant syndromes. Clinical observation” - N. A. Suponeva (Nervno-Myšečnye Bolezni, 2018)
.